2022
DOI: 10.3390/nu15010147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Infant Formula on Weight Gain, Body Composition, Safety and Tolerability to Infants: The INNOVA 2020 Study

Abstract: Exclusive breastfeeding is recommended for the first six months of life to promote adequate infant growth and development, and to reduce infant morbidity and mortality. However, whenever some mothers are not able to breastfeed their infants, infant formulas mimicking human milk are needed, and the safety and efficacy of each formula should be tested. Here, we report the results of a multicenter, randomized, blinded, controlled clinical trial that aimed to evaluate a novel starting formula on weight gain and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
1
11
0
1
Order By: Relevance
“…In our study, the main comparison was made using the BF group. A detailed description of the effects of the different groups on weight gain, body composition, safety, and tolerability has been provided elsewhere [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, the main comparison was made using the BF group. A detailed description of the effects of the different groups on weight gain, body composition, safety, and tolerability has been provided elsewhere [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Rivera-Pinto approach [ 28 ], we observed that the INN formula group has a higher AUC value than the BF group, all of which are compared using the ROC curve. The safety of the INN formula group and its impact on the body composition group was described elsewhere [ 24 , 25 ]. It is believed that the modifications made to the INN formula are intended to produce a similar effect to breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations